Penerapan Etika Bisnis Syariah Pada Usaha Mikro Kecil Menengah (Umkm) Masa Pandemi Covid-19 di Pasar Swadaya Gotong Royong Masyarakat Batumarta Desa Baturaden Kecamatan Lubuk Raja Kabupaten Ogan Komering Ulu - Samsul Bahrri; Maya Panorama (Medina-te : Jurnal Studi Islam, 2021)
Basic problems research this is how the application of the ethical principles of a business according to islamic syariah on micro business in the village baturaden ( kecamatan kabupaten oku the bottom of the king .As for the purpose of this study is to find the application of islamic business of ethical principle at a venture mikro.jenis this research is descriptive qualitative research was conducted research which is a devoted to described analyzed the phenomenon of events , social activities , attitude , trust , perception , the minds of the american individually as well as groups .Research object is the owner of micro business in the market swadaya gotong royong village community batumarta baturaden oku the bottom of the king . Data collection by means of observation , interview , documentation , and such .And is poured into table then analysis technique data using the qualitative method descriptive by pulling a conclusion by using a technique inductive , deductive , and comparative .The research results show that has not yet been fully know , understand and apply .It was because the small and medium businesses umkm players culinary in the market swadaya masyarakat gotong royong batumarta inside do the business practices employed in truth and do not have not been in accordance by islamic syariah